Workers of the world, unite! Franchise extensions and the threat of revolution in Europe, 1820-1938 - Toke S. Aidt; Peter S. Jensen (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper tests the hypothesis that the extension of the voting franchise was caused by the threat of revolution, as suggested by Acemoglu and Robinson [Quarterly Journal of Economics 115, 1167-1199, 2000]. We approximate the threat of revolution in a given country by revolutionary events happening in neighboring countries. We investigate the relationship between this new measure of the threat of revolution and measures of suffrage reform in two samples of European countries covering the period from 1820 to 1938. We find strong support for the 'threat of revolution theory'. We also find some evidence that war triggered suffrage reform, whereas other theories of the extension of the franchise, including 'modernization theory', receive little support.
Keywords: D70; P16; 330; the extension of the voting franchise; democracy; threat of revolution; suffrage; Demokratisierung; Politische Unruhen; Wahlrecht; Europa